Pengaruh Penggunaan Metode Permainan Kartu Bilangan terhadap Motivasi dan Hasil Belajar Siswa Materi Pecahan - FARUQ, DUKAN JAUHARI (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
This study aims to determine the effect of the use of game card number method on the motivation and student learning outcomes on the fractional material in the fourth grade MI Hasyim Asy'ari Pontang Ambulu Jember. The research method used is quasi experimental research with the number of students experiment class and control each 20 students. Data collection techniques that is by using pretes and postes. The data analysis used is T test. The result of data analysis with T test at level of 95% confidence indicates that student learning result of experiment class that use game method of number card better than student in control class that does not use game method of number card. From the results of the above analysis the researchers drew the conclusion that the students' learning outcomes using the program of the card number game method is higher than the students who do not use the method of card numbering. So the number card game method can be used as an alternative of learning media that can improve the motivation and student learning outcomes